Physiology and Pathophysiology of Proteinase-Activated Receptors (PARs): PAR-2 as a Potential Therapeutic Target - Toru Kanke; Toshiaki Takizawa; Mototsugu Kabeya; Atsufumi Kawabata (Elsevier, 2005)
PAR-2 is the second member of the family of proteinase-activated receptors activated by trypsin, tryptase, and several other serine proteinases. In order to evaluate the therapeutic potential for PAR-2, we have performed studies on PAR-2-mediated signal transduction and investigated the effects of PAR-2 gene deficiency in disease models. In addition to the G-protein-coupled receptor-mediated common signal transduction pathways, inositol 1,4,5-trisphosphate production and mobilization of Ca2+, PAR-2 can also activate multiple kinase pathways, ERK, p38MAPK, JNK, and IKK, in a cell-type specific manner. The studies using PAR-2-genedeficient mice highlighted critical roles of PAR-2 in progression of skin and joint inflammation. We also describe the development and evaluation of potent and metabolically stable PAR-2 agonists in multiple assay systems both in vitro and in vivo. The structure-activity relationship analysis indicated the improved potencies of furoylated peptides. Furthermore, the resistance of the furoylated peptide against aminopeptidase contributed to the highly potent and sustained effects of the peptide in vivo. These studies suggest the potential therapeutic importance of PAR-2 in inflammatory diseases. Also, the PAR-2-gene-deficient mice and the potent and metabolically stable agonists are shown to be useful tools for evaluating the potency of PAR-2 as a therapeutic target. Keywords:: proteinase-activated receptor (PAR)-2, mitogen-activated peptide kinase, PAR-2-gene-deficient mice, PAR-2-activating peptide